Impact of neurotrophic factors combination therapy on retinitis pigmentosa. Issue 11 (November 2020) - Yin, Xiaobei; He, Ting; Chen, Rui; Cui, Hui; Li, Genlin
Objective: We aimed to determine the location of neurotrophic receptors tropomyosin receptor kinase (Trk)B, TrkC, and ciliary neurotrophic factor receptor (CNTFR)α in the retina of retinal degeneration ( rd ) mice and to explore the dynamic changes of B-cell lymphoma-2 (Bcl-2), Bcl-2-associated X-protein (Bax), and microtubule-associated protein light chain 3 (LC3) expression and ultrastructure in the retina of rd mice intravitreally injected with neurotrophic factors. Methods: Rd mice aged 2 and 3 weeks post-natally (PN) received intravitreal injections of neurotrophic factors. Two weeks later, their retinas were harvested for the detection of Bax, Bcl-2, and LC3 mRNA and protein expression. Results: TrkB and TrkC expression levels were lower at 3 weeks PN compared with 0, 1, and 2 weeks PN, but CNTFRα expression was still detected in certain layers. The three receptors were expressed in different retinal layers at the same timepoint. Bax expression was downregulated in, rhBDNF + rhCNTF, rhBDNF + rhNT-3, groups 2 weeks after intravitreal injection; Bcl-2 expression was upregulated in the rhBDNF + rhCNTF + rhNT-3 group at PN-4w; and LC3 expression was upregulated in rhBDNF + rhCNTF + rhNT-3 groups. Conclusions: The combined use of neurotrophic factors had a more significant effect on Bax, Bcl-2, and LC3 expression than the same factors used alone.